PENGARUH MODEL PEMBELAJARAN CIRCUIT LEARNING DISERTAI LKPD TERHADAP HASIL BELAJAR FISIKA PESERTA DIDIK KELAS XI MIPA SMA KARTIKA I-5 PADANG - Mega Mega (Horizon, 2021)
This study aims to determine whether there is an effect on the physics learning outcomes of students by applying the Circuit Learning model instead of using a scientific approach in class XI MIPA at SMA Kartika I-5 Padang. This type of research is a quasy experiment, with a randomized control group only design. This research was conducted in two sample classes, namely class XI MIPA 2 and class XI MIPA 4 at SMA Kartika I-5 Padang. The instruments used in this study were the essay test and the observation assessment sheet. Based on the results of data analysis, it was known that both sample classes were normally distributed and not homogeneous at the real level = 0.05. The test statistic used was the two-parts t test. Based on the results of the calculation, hypothesis testing is obtained = −7,25 withttabel = 2,04 because - ttabel < 1 < ttabel with = 2.04 because - then reject H0 and H1 is accepted where the hypothesis is accepted. Based on the results of the analysis, it can be seen that the experimental class activities are better than the control class learning activities. So it can be concluded that hypothesis in this study is physics learning. The outcomes learning of students using the Circuit Learning model accompanied by LKPD on students' physics learning outcomes were better than the physics learning outcomes of students who used scientific learning models in class XI MIPA SMA I-5 Kartika Padang.